Column-based method to simultaneously extract DNA, RNA, and proteins from the same sample - Jorge M. Tolosa; John E. Schjenken; Theodora D. Civiti; Vicki L. Clifton; Roger Smith (BioTechniques)
We describe a procedure for the simultaneous extraction of proteins and nucleic acids from the same experimental sample allowing for direct correlations between genetic, genomic, and proteomic data. This approach, using commercially available column-based nucleic acid extraction kits, requires no hazardous chemicals and is a quick, reliable, and consistent method for concomitant protein extraction. Buffer choice is critical to completely solubilize all proteins in the sample. Proteins solubilized in radioimmunoprecipitation assay (RIPA) buffer did not represent the entire profile when compared with conventionally extracted proteins using the same buffer at the one-dimensional (1-D) sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) level, however, proteins extracted from the columns and solubilized in a two-dimensional (2-D) electrophoresis lysis buffer showed a similar profile to conventionally extracted proteins when analyzed at both the 1-D and the 2-D level. We further showed that proteins extracted using these methods were compatible with Western blot analysis. This technique provides a simple and effective way to analyze protein and nucleic acids simultaneously from the same sample without affecting yield and quality.